Tenant satisfaction level on air conditioning performance at shopping mall / Syanaz Nasar and Mohamad Haszirul Mohd Hashim - Nasar, Syanaz; Mohd Hashim, Mohamad Haszirul (2023)
This research endeavours to address maintenance challenges within air conditioning systems at Malaysian shopping complexes, aiming to bolster building management efficacy through a tailored maintenance management program. By conducting a comprehensive review of literature, surveys, and interviews, tenant satisfaction concerning air conditioning performance will be assessed. Discoveries will shed light on critical maintenance obstacles, failure modes, and effective strategies. The study's aspiration is to contribute to sustainable building practices by optimizing air conditioning maintenance, curbing energy consumption, and enhancing tenant comfort. The envisaged outcome encompasses a holistic maintenance management program, offering actionable steps and protocols to elevate air conditioning system performance, extend its operational life, and fulfil client requisites. This inquiry seeks to bridge the gap between maintenance protocols and tenant contentment, yielding benefits for both building management and occupants amid challenging climates. In conjunction, the study underscores how addressing hot climate air conditioning hurdles not only ensures comfort and safety but also advances sustainable, energy-efficient building operations while prioritizing demanding customers' contentment and desired performance levels.